Implementation of a Multiple Intelligence-based Learning Model for Students with a Tendency to be Slow Learners - Fillia, Ayu; Kaltsum, Honest Ummi (Universitas Muhammadiyah Surakarta, 2023)
The aim of this research is to describe the process of selecting a learning model, implementing the multiple intelligence learning model for students who tend to be slow learners, the obstacles faced by shadow teacher, and solutions to overcome the obstacles that exist at MIM PK Kartasura. This research method is qualitative, with a descriptive approach and a phenomenological research type. This study used data collection through observation, interviews, and documentation. The data analysis technique in this research uses the interactive model from Miles and Huberman with the following steps: data reduction, data presentation, and drawing conclusions. The subjects of this research were shadow teacher, who accompanied Slow Learner students in class 2, the homeroom teacher for class 1, and the head of the madrasah. The research results show that the implementation of the multiple intelligence learning model for slow learners has been adapted to the results of the students' Multiple Intelligence Research (MIR), namely the lecture method combined with the demonstration or practice method. There is no significant difference in the learning methods used by slow learners and other students; it's just that slow learners are accompanied by shadow teacher to use a special approach in doing their assignments. The obstacle that shadow teacher experiences is that students do not concentrate enough when learning. To overcome this obstacle, shadow teacher provides a solution, namely by inviting students to study in separate rooms and doing ice-breaking so that students can concentrate again.